PENGARUH PENGELUARAN KONSUMSI RUMAH TANGGA TERHADAP PERTUMBUHAN EKONOMI PROVINSI SUMATERA BARAT TAHUN 1988-2023 - Adelia Rizki Ariani; Amsah Hendri Doni (CV. Adiba Aisha Amira, 2025)
This study examines the mismatch between increased economic development and household consumption West Sumatra from 1988 to 2023. Employing a quantitative method with time series data from BPS (Statistics Indonesia), the research targeted to explore the contribution of each predetermined variable. The learning results show that household consumption contributes optimally to economic development from sig 0.033 and participation of 13.5%. The difference of 86.5% is contributed by other aspects such as government spending, investment, exports, and imports. These findings affirm the importance of household consumption, although its role is limited in driving overall economic growth.